A study on maternal factors affecting low birth weight in institutional deliveries - A., Chaithra; Chiniwar, Mahantappa A.; Menasinkai, Sharada B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Low birth weight is defined as birth weight below 2500 mg. WHO states prevalence of LBW is 26%. LBW babies are more prone for neonatal morbidity and mortality. 1) To assess various factors like maternal age, height, education, socioeconomic status on the birth weight of the baby. 2) To assess obstetric factors like parity, gestational age, antenatal care, anemia, hypertension on the birth weight of the newborn. Methods: A hospital bound cross sectional study done at the tertiary care centre. Study was done for a period of 2 months from 1st June to 30th July 2019 in Adichunchanagiri Institute of Medical Sciences and Research Hospital a rural medical college in Karnataka. Maternal data were collected and baby weight was recorded soon after birth on weighing scale. Results: There were 65 births during the study period. There were 13 babies weighing less than 2500 gm. Prevalence of LBW was 20%. 43.47% mothers were aged between 18 to 25 years and 7.14% were more than 25 years. 30.4% mother’s height was between 140 to 150 cm and 14.2% were more than 150 cm. Regarding maternal education, 15.3% degree, 24.1% PUC, 15% High school and 33.3% were primary school level. Regarding socioeconomic status 22.2% low, 25% lower middle, 18.7% middle class, 18.7% belonged to upper middle class. Regarding gestational age 50% were <37 weeks, 15.5% between 37-42 weeks, 10% were 42 weeks.73.8% women had normal BP, 21.5% were prehypertensive, 4.6% had PIH. Conclusions: Low birth weight is one of the important factors in infant morbidity and mortality. Maternal health was important factor in delivery of low birth babies. Maternal height, sex of baby, mode of delivery has no role in low birth weight babies.